Social Media and Poverty: Paradoxes of Communicating Poverty Issues on Social Media - Wahyunengseh, Rutiana Dwi; Hastjarjo, Sri; Suharto, Didik G. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
From the democratic theory perspective, social media is a means to improve collaborative public governance between government, society, and business sector, in order to ensure effective public issues management as well as public services. On the other hand, there are preconditions for the effective use of media social; in the context of addressing poverty issues, these preconditions have potential to generate certain paradoxes. This article aims to answer a question “Is the use of social media effective to the poverty alleviation mainstreaming issue?” This study was conducted in one of the cities that won Smart City Award in Indonesia; using content analysis on the "Monggo Lapor" Facebook group combined with the mapping of Local Government Apparatus and poor people group’s perception on the use of social media for poverty issue through focus group discussion. The data then was analyzed using Institutional Theory approaches to identify the paradoxes that emerge from the using of social media in process of communication addressing poverty issues. The result shows that poverty issues were marginalized in the discussion using Facebook group, because of the culture of the bureaucracy in the local government and the culture of the society. The paradoxes arising were, i) democratic-elitist; ii) functional-artificial ones. The emerging paradoxes resulted from the inconsistency of the Local Government in implementing e-government for addressing poverty issues and the elitism in using the social media as a tool for power control by society. Social Media “Monggo Lapor” has not functioned intensively as the means of expressing voice and communicating between people and government for poverty issue, but it had functioned intensively for non-poverty issues, so that non-poor group enjoy its usefulness more. It indicated that the group with excess power had a higher ability of using social media. This paper recommends further research focusing on building social media readiness model, particularly for developing an inclusive regulation for poverty alleviation.